Peran Perencanaan Pensiun, Religiusitas, Afek Positif, dan Afek Negatif terhadap Kecemasan Pensiun - Timba Imas J.Y.K. Sitorus; Neila Ramdhani (University of Merdeka Malang, 2014)
The purpose of this study was to know the effect of retirement planning, religiosity, positive affect and negative affect on retirement anxiety on employees of PT.Perkebunan Nusantara (PTPN) III Medan area. The sample size of this study was 100 people taken 20% of the total population. Data collection in this study using four scales namely retirement anxiety, retirement planning, religiosity, and PANAS (positive negative afect Affect scale). The results of multiple regression analysis showed jointly retirement planning, religiosity, positive affect and negative affect may be a predictor to predict retirement anxiety by 31.3% to R = 0.559 (p = 0.001). Retirement planning can be a predictor retirement anxiety of 6.3% (p = 0.012), the religiosity of 6.3% (p = 0.013), positive affect by 7.2% (p = 0.007), and negative affect by 26.3% (p = 0.001)